Mormon Missionary Experiences and Subsequent Religiosity among Returned Missionaries in Utah - Grace Chou, Hui-Tzu (Social sciences and missions, 2013)
This qualitative research examined Mormon missionary experiences and their impacts on the religiosity of returned missionaries living in Utah. Based on open-ended surveys completed by those who served a mission for the Mormon Church, this research analyzed how missionary experiences increased the religiosity of most missionaries, as well as reasons why some respondents felt their missionary experiences decreased their religious level. This paper also examined the missionary experiences of those who later dropped out of Mormonism – why their missionary experiences failed to strengthen their commitment while they convinced others to join the Mormon Church. This paper found that men and women faced different challenges during their mission, and mission experiences also affected men’s and women’s religiosity differently. In addition, although those who served in Western Europe faced the highest rate of rejection during their mission, they reported higher religious and spiritual levels than their counterparts. The paper concludes with the development of a grounded theory arguing that the impact of the Mormon missionary experiences on missionaries’ subsequent religiosity corresponds to a process of maximizing social acceptance and minimizing social rejections among various social groups.